Introduction and Uptake of New Medical Technologies in the Australian Health Care System: A Qualitative Study - Gallego, G.; Casey, R.; Norman, Richard; Goodall, S. (Elsevier Ireland Ltd, 2011)
Objective: The aim of this study was to explore the views and perceptions of stakeholders about the current national health technology assessment process conducted by the Medical Services Advisory Committee (MSAC) and its role in the uptake and diffusion of new medical technologies in Australia.Methods: Data collection occurred over a nine month period (August 2008–April 2009). Twenty in-depth, semi-structured interviews were conducted with individuals from four stakeholders groups: (i) MSAC members and evaluators, (ii) academic and health technology assessment experts, (iii) medical industry representatives and (iv) medical specialists. Interviews were digitally recorded, transcribed verbatim and coded using a constant comparative method.Results: Respondents expressed a consensus opinion that the MSAC process is generally fair and transparent, and has been increasingly so over time. The process was described as “flexible” and “intuitive” yet also “idiosyncratic” due to the nature of the technologies being appraised. Approval by MSAC was generally reported to be increasingly important once a technology becomes more widely used. While successful MSAC approval was felt to be important for widespread distribution of a new technology, it was viewed more as a “facilitator of the uptake of new technologies” as opposed to a primary “driver” of technology uptake. Instead, other factors were identified as providing the actual impetus for the uptake of new technologies, with MSAC approval and reimbursement eventually helpingfacilitate more widespread diffusion.Conclusions: MSAC’s decision making process is perceived as fair but with room for improvement. Its role in the uptake and diffusion of new medical technologies in Australia is limited. MSAC does not act as a barrier to significant market penetration of new procedures and medical technologies. However reimbursement is a trigger for increased use.